Decentralized Bargaining : Its Problems and Direction in Ontario and the Western Provinces - Muir, J. (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1971)
This paper is directed to the bargaining structure issue and examines the problems and direction of decentralized bargaining in British Columbia, Alberta and Ontario